The role of a polycaprolactone stimulator in the facial rejuvenation process - Gonzalez-Botello, Ana Lorena (Aesthetic Medicine, 2024)
Background: Aging is a process that mainly affects human fibroblasts since they have a limited ability to divide. In general, cells lose their proliferative capacity and enter a cell slowdown, also known as cellular senescence. This review focuses on non-surgical techniques for both functional and cosmetic facial rejuvenation, with particular attention to polycaprolactone (PCL) fillers as an effective collagen stimulator. Aim: The aim of this study is to evaluate the efficacy of polycaprolactone stimulators in facial rejuvenation by assessing improvements in skin texture, volume restoration, and overall aesthetic outcomes. Methods: A systematic review was conducted between May 2022 and October 2023, involving a comprehensive analysis of twenty-five articles. Results: The studies presented below, each designed to address various aspects related to PCL dermal fillers, are extensively analyzed, encompassing enhancements in dermal properties, histopathological insights, patient satisfaction and safety, the assessment of potential complications, and combination therapies. Conclusion: PCL is a safe and effective material for skin rejuvenation, and it is a viable choice in the realm of aesthetic and functional enhancements, addressing the perennial quest for youthful and rejuvenated appearances with minimal risks and maximal patient satisfaction.